Contrastive Analysis of the Present Tense in Serbian and English - Kukić, Marko E. (Collection of Papers of the Faculty of Philosophy in Priština, 2024)
This paper aims to comprehensively analyze the syntactic-semantic features inherent in the present tense in the Serbian language, juxtaposed with an exploration of their counterparts in the English language. Delving into the intricacies of specific meanings, we systematically incorporate indicative, relative, and modal meanings. Beyond delineating the fundamental constructs of the present tense, particular emphasis is placed on the temporal dimension, elucidating the property of the present tense not only to refer to past events but also to indicate future actions. Addressing the complex nature of tense as a linguistic category, the study extends its analytical framework to the category of aspect, thereby elucidating the varied verb forms of the English present tense, including the progressive, perfect, and perfect-progressive aspects. Employing a methodology combining contrastive and descriptive analysis, the research explores the degrees of equivalence inherent in the present tense, in an attempt to discern and articulate corresponding counterparts in English for each specified syntactic-semantic nuance. Upon the completion of the analysis, it was concluded that both linguistic systems convey specific syntactic-semantic meanings, attesting to a considerable degree of equivalence. This analysis underscores the attributes shared by both languages, indicating a high degree of alignment between their linguistic structures.